A practical method for predicting the propulsive performance of energy efficient ship with wave devouring hydrofoils at actual seas. (November 2014) - Feng, Peiyuan; Ma, Ning; Gu, Xiechong
The Energy Efficiency Design Index (EEDI) is made mandatory by the International Maritime Organization to reduce emissions of greenhouse gases from international shipping. In this study, wave energy recovery using a pair of hydrofoils fixed at the ship bow to realize energy efficient propulsion is proposed. This so-called wave devouring hydrofoil (WDH) functions both as an anti-motion fin and a wave energy device, which can help reduce the ship wave added resistance, heave and pitch responses. To evaluate its performance, the coupled interaction between the hydrofoils and the ship under head sea condition is first modeled in the frequency domain together with the evaluation of wave added resistance in the presence of the WDHs. Model test is then conducted using a sample containership. Both the beneficial effect of the WDHs and the validity of the numerical model are proved. The peak response is reduced by 80%, 30% and 25% for added resistance, heave and pitch, respectively. This model is then further modified to include other wave directions. Based on frequency domain results, short-term and long term predictions of speed loss, engine power increase and propeller racing are performed for a 3100TEU containership along her transportation route. The merit of this prediction model is that the hull -propeller -engine interactions is considered from a system balance point of view. It is demonstrated that the WDHs can contribute to the energy-efficient ship propulsion at actual seas, achieving a slight reduction of EEDI and ensuring less speed loss and propeller racing.